I.iv.3 Minutes, - Labour Party (Ireland) (1973)
Minutes of four meetings of the Party Officers which took place between 5 Apr 1973 – 2 Nov 1973. Also includes minutes of a meeting of the Party Officers with the General Officers and trustees of the Irish Transport and General Workers Union (ITGWU), dated 1 Jan 1973. (5 pp)